2009
DOI: 10.1002/fam.994
|View full text |Cite
|
Sign up to set email alerts
|

Experimental fire analysis of steel‐to‐timber connections using dowels and nails

Abstract: SUMMARYThe paper describes and discusses the results of an extensive testing programme on the structural behaviour of timber connections under ISO-fire. The results of reference tests performed at normal temperature are also presented. From the variety of timber connections multiple shear steel-to-timber connections with dowels and slotted-in steel plates and connections with steel side plates and annular ringed shank nails were experimentally studied. Particular attention was given to the analysis of the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…Erchinger [10,14] performed a series of fire resistance tests on steel-to-timber dowelled connections. The tests consisted of 18 fire tests under standard ISO-fire exposure and 25 tests conducted at ambient temperature.…”
Section: Fire Behaviour Of a Steel Connection Between Timber Structurmentioning
confidence: 99%
“…Erchinger [10,14] performed a series of fire resistance tests on steel-to-timber dowelled connections. The tests consisted of 18 fire tests under standard ISO-fire exposure and 25 tests conducted at ambient temperature.…”
Section: Fire Behaviour Of a Steel Connection Between Timber Structurmentioning
confidence: 99%
“…For comparison, Lau [6] found that the improved fire resistance for bolted SWS connections and the nailed steel-wood-steel connections were about 9.9 min and 8.2 min, respectively. Frangi [25] stated that the protection of a 2 mm thick intumescent paint to steel side plates increased the fire resistance of nailed SWS connections by about 18 min.…”
Section: Intumescent Paintmentioning
confidence: 99%
“…The main objective of this work is to present the analytical formulation that can be applied in design of wood connections. Wood connections have been investigated due to their impact in construction engineering in terms of strength, ductility, and all capability to increase the structural performance in service [5][6][7]. In heavy timber structures, doubleshear wood connections with steel fasteners are widely used to assembly structural members and transfer loads [5].…”
Section: Introductionmentioning
confidence: 99%